Interaction between uterine natural killer cells and extravillous trophoblast cells: effect on cytokine and angiogenic growth factor production - Lash, Gendie E.; Naruse, Katsuhiko; Robson, Andrew; Innes, Barbara A.; Searle, Roger F.; Robson, Stephen C.; Bulmer, Judith N. (Human reproduction (Oxford), 2011)
BACKGROUND Uterine natural killer (uNK) cells are a major source of cytokines and angiogenic growth factors (AGFs), with AGF levels decreasing and cytokine levels increasing with gestational age. The factors that regulate AGF and cytokine secretion are unclear but may involve interactions between uNK cells and extravillous trophoblast (EVT) cells. We hypothesize that uNK cell interaction with EVT cells alters their cytokine and AGF secretion. METHODS Ex vivo co-cultures of uNK cells with either EVT (irradiated or fresh) or villous cytotrophoblast (CTB; control cell type) cells isolated from the same patients at 8–10 or 12–14 weeks gestational age (n = 10 each group) were established. Co-cultures were established with either direct contact between the different cell types or with the cells separated by a 0.4 µm filter. AGFs and cytokines were measured in cell culture supernatants using multiplex analysis (FAST Quant) or ELISA. RESULTS Secretion of angiopoietin-1 (P< 0.006) and vascular endothelial growth factor-C (P< 0.001) by uNK cells was lower when these cells were co-cultured, either directly or indirectly, with both trophoblast cell types at both gestational ages tested compared with when cultured alone. In contrast, interleukin (IL)-6 (P < 0.0001), IL-8 (P < 0.0001) and transforming growth factor-β1 (P < 0.002) were decreased only in direct uNK/EVT and uNK/CTB co-culture conditions at 8–10 and 12–14 weeks gestational age. CONCLUSIONS AGF and cytokine secretion was reduced after co-culture of uNK cells and both EVT and CTB cells. It remains unclear whether uNK cell AGF and cytokine production was reduced after co-culture with trophoblast cells (EVT or CTB) or whether trophoblast cell (EVT or CTB) AGF and cytokine production was reduced after co-culture with uNK cells. Local production of AGFs and cytokines in the placental bed may be lowered when uNK cells come in direct contact with EVT cells.